Burden of Mothers’ Care for Children with Colostomy at Baghdad Medical City Teaching Hospital - Shauq, Adraa (Iraqi National Journal of Nursing Specialties, 2015)
Objective(s): To assess the burden of mothers` care for child with colostomy and find out relationships between child and mother socio-demographic data with mothers` burden. Methodology: a descriptive study was conducted from 1 August 2013 to 1 September 2014. The sample consisted of 100 children and their mothers at Baghdad Teaching hospital in Baghdad city. A questionnaire was prepared based on the previous literature review, meeting mothers of children with colostomy, and the Zarit Burden Interview scale. Data has collected through the application of questionnaire and interview techniques. Results: The data shows that mothers suffer from moderate burden socially, psychologically, financially, and overall burden of care. More than one third of mothers are within 38-40 years old, illiterate, with four children. Majority of them are unemployed and visit their children’s physicians regularly. More than half of families have somewhat sufficient monthly income and their child within 1-4 years old. Most of children are male and suffer from skin excoriation as complication. In addition, numbers of children in the family, physician’s follow-up, and mothers` age effects on mothers` social burden. Child’s age negatively correlates with financial burden. Ultimately, mothers’ age and their level of education, and family monthly income effect on mothers` psychological burden. Recommendations: mothers of child with colostomy experience a multitude of emotions and changes in their lives, often carrying caregiving burden. They become the experts on their child’s care and should be empowered and supported in their efforts. The level of mothers’ education should be increase and awareness about family planning.